2013
DOI: 10.1007/s11433-013-5209-z
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation into the icing and melting process of a water droplet impinging onto a superhydrophobic surface

Abstract: The freezing and melting process of a small water droplet on a superhydrophobic cold surface was investigated using the Laser Induced Fluorescence (LIF) technique. The superhydrophobic surface was prepared using a sol-gel method on a red copper test plate. From the obtained fluorescence images, the phase transition characteristics during the freezing and melting process of a water droplet were clearly observed. It was found that, at the beginning of the droplet freezing process, liquid water turned into ice at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…Besides, a large amount of air bubbles appeared and was trapped in the ice bead. Due to the formation of air bubbles, the liquid-solid interface could not be discerned as clearly as our previous studies [49,50,52]. At t = 690.0 s, a cusp point was found to form on the top of the ice bead, which marked the completion of the freezing process.…”
Section: Droplet Freezing Processcontrasting
confidence: 68%
See 2 more Smart Citations
“…Besides, a large amount of air bubbles appeared and was trapped in the ice bead. Due to the formation of air bubbles, the liquid-solid interface could not be discerned as clearly as our previous studies [49,50,52]. At t = 690.0 s, a cusp point was found to form on the top of the ice bead, which marked the completion of the freezing process.…”
Section: Droplet Freezing Processcontrasting
confidence: 68%
“…In the present study, the time interval between the moment when the circulator was turned off and the moment while the ice bead melt completely was defined as the melting time of the ice bead. Thus, the total melting time of the ice bead for this case was about 700 s. It should be noted that Jin et al [49] obtained the melting process of a water droplet on a horizontal superhydrophobic surface. Their results indicated the solid-liquid interface kept almost parallel to the superhydrophobic surface during the melting process of ice bead.…”
Section: Ice Bead Melting Processmentioning
confidence: 71%
See 1 more Smart Citation
“…on wind turbines, airplane wings, and roads, calls for a better understanding of the freezing process for water droplets on cold surfaces. Previous research has identified a number of factors important to the freezing process such as the temperature of the cooling surface, T p [1], the size of the droplet [2] the impact of free and forced convection [3,4], the roughness and wettability of a surface [5], the freezing on superhydrophobic surfaces, e.g. [6], the effect of an inclined surface [7][8][9], internal heat transfer [10,11] and internal flow [12].…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of this layer remains relatively constant through the melting process, measuring approximately <0.05 mm. All remaining water converted from solid to liquid accumulates below the floating ice block, and as the ice crystal shrinks it releases contained air volumes and MWCNT clusters into the liquid beneath [42]. The air bubbles either accumulate along the bottom edge of the ice or rise to the top of the droplet through the thin liquid shell.…”
Section: Convective Currents Within the Liquid Melt Regionmentioning
confidence: 99%